Vestibular Evoked Myogenic Potentials in Patients With Vestibular Migraine. Issue 2 (February 2015) - Zaleski, Ashley; Bogle, Jamie; Starling, Amaal; Zapala, David A.; Davis, Laurie; Wester, Matthew; Cevette, Michael
Abstract : Objective: Literature investigating otolith reflexes in patients with vestibular migraine (VM) is variable and primarily describes the descending saccular pathway. This research aimed to study ocular vestibular evoked myogenic potential (oVEMP) and cervical vestibular evoked myogenic potential (cVEMP) prevalence and response characteristics in patients with suspected VM and in control patients. The purpose is to assess vulnerabilities within the ascending utricular and descending saccular pathways in the VM population. Study Design: Retrospective study Setting: Tertiary academic referral center Patients: 39 adults with VM, 29 control patients Main Outcome Measure(s): Air conducted oVEMPs and cVEMPs measured with 500 Hz tone burst stimuli Results: Age of headache onset was most often in childhood or adolescence, with dizziness onset occurring later. The rate of bilaterally absent oVEMPs was significantly higher (28%, p < 0.01) in the VM group compared with the control group (0%). oVEMP amplitude asymmetry ratios were significantly higher for the definite VM ( p < 0.01) and probable VM ( p = 0.023) groups than the control group. Eleven patients also had history of concussion; they were significantly more likely to demonstrate bilaterally absent oVEMPs ( p < 0.01) in comparison to the control patients. When VM patients with a history of concussion were omitted from analysis, differences in oVEMP amplitude asymmetry ( p < 0.01) and bilateral oVEMP absence remained significant ( p = 0.015). There were no differences in the rate of bilateral cVEMP presence or response parameters between VM and control groups. Conclusion: VEMP presentation differs for some patients diagnosed with VM. The higher rates of abnormal oVEMPs may suggest greater vulnerability within the ascending utricular–ocular pathway in patients with VM.